Mar de cana, deserto verde? Dilemas do desenvolvimento sustentável na produção canavieira paulista. - Gonçalves, Daniel Bertoli (2005)
The role of the sugar-cane production in the regional sustainable development has been lifting a lot of controversy on those last years. While the Brazilian sugar-cane sector is prominence in the international market, offering products of great value in terms of environmental sustainability, the workers and the local communities that live together with the sugar-cane production system alleges another reality, marked by the unemployment, bad field work conditions, environmental pollution, and bad distribution of income. This work makes an analysis about the social and environmental situation of the sugar-cane production in the sugar-cane area of the Hydrographic Basin of the river Mogi-Guaçú, main sugar-cane area of the State of Sao Paulo, identifying the main obstacles that this activity presents for the sustainable development, and the proposals and alternatives that exist for the improvement of the environmental and social conditions of this activity in the area. The analysis shows that the situation of environmental and social unsustainability in that meets the regional sugar-cane production system it will only be able to be solved through the consolidation of a regulatory endowment built by the group of the local society.